Public Service Innovation in Public Administration: Case Analysis of E-Government Implementation in Surabaya City Government - Suhardoyo; Meithiana Indrasari; Safutra Rantona; Ike Devi Sulistyaningtyas; Tito Rachmanto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The implementation of e-government has emerged as a critical catalyst for public service innovation, with the primary goals of enhancing efficiency, transparency, and citizen participation in public administration. This qualitative case study explores the e-government initiatives implemented by the Surabaya City Government, establishing Surabaya as a leader in digital governance within Indonesia. Despite the global and national focus on e-government systems, a substantial research gap persists in understanding the specific challenges and outcomes faced by local governments, particularly within Indonesia's socio-political framework. Employing qualitative methods, such as in-depth interviews with government officials and citizens, this study analyzes the implementation strategies, the impact on public service delivery, and the influence of government officials, technological infrastructure, and organizational culture on the success of e-government. The findings indicate that while e-government has enhanced administrative efficiency and service accessibility, significant challenges, including digital literacy, infrastructural limitations, and political resistance, remain. Additionally, although citizen engagement has improved, certain population segments continue to face barriers due to the digital divide. This research advances the existing literature by providing a detailed examination of local e-government implementation and offering practical recommendations for overcoming challenges in similar settings.